The Quality and Heat Stability Comparison of Packaged Cooking Oil and Bulk Cooking Oil - Rismaya, Rina; Kurniawan, Andhi Dwi (Jurnal Sains dan Teknologi Pangan, 2023)
Bulk Cooking Oil (BCO) is still preferred by people because its price is cheaper than Packaged Cooking Oil (PCO). The price difference may be due to the difference in quality and heat stability during cooking at high temperatures. This study aimed to compare the quality and heat stability of BCO and PCO based on Free Fatty Acid (FFA) and Iodine Value (IV). This study used a completely randomized factorial design 2x5 with cooking oil types (package and bulk) and temperature (40, 80, 150, 200 and 250℃) as factors, while oil quality indicators as responses evaluated were FFA and IV. The results showed that the quality of PCO was better through significantly lower FFA and higher IV than BCO. The higher the temperature, the higher the FFA, while the lower the IV. Based on FFA results, BCO and PCO had the same level of heat stability, where the FFA of both significantly increased at 150℃. Meanwhile, the IV results showed that BCO had better heat stability, where the IV of BCO significantly decreased at higher temperatures (200ºC) than PCO (150ºC). In conclusion, PCO was better in quality based on FFA and IV, but not better in heat stability than BCO.